EXPERIMENTAL ANALYSIS OF ADIABATIC FLOW OF NON-AZEOTROPIC MIXTURE R407c THROUGH A CAPILLARY TUBE - Ortiz, L. B.; Motta, S. Y.; Braga, S. L.; Parise, J. A. R. (Revista de Engenharia Térmica, 2001)
The present work is related to the experimental evaluation of adiabatic flow of R22 and R407c, a nonazeotropic mixture, through a capillary tube. An experimental apparatus was erected to control and measure flow conditions across the capillary tube. Condensing temperature and degree of subcooling, i.e. upstream conditions, were kept within the range of 31oC and 45oC , and 7 e 24oC, respectively. Results have shown that R22 and R407c have similar performance, for giving operating conditions. One single geometry was tested. The capillary tube had a length of 1.3 m, an internal diameter of 0.81 mm and a roughness of 0.7 mm.